Zanik prywatności jako narastający problem społeczeństwa informacyjnego - Wysokińska, Aleksandra (Człowiek i Społeczeństwo, 2015)
Since the beginning of its existence, the Internet has been almost synonymous with anonymity, giving unfettered opportunities to create a virtual identity. A lot has changed after the introduction of the era of Web 2.0. The network has become primarily a tool of communication with friends and loved ones, a place of socializing and a giant, constantly expanding photo gallery. People in society, along with benefiting from the growing possibilities of the web have divulged more and more information about themselves. Today, in a time of scandals revealing states spying on their own citizens, and social networks constantly changing their terms of privacy, no one believes in the anonymity of the Internet. This paper is aimed at presenting the most important issues related to the concept of network surveillance, with an emphasis on the problem of online privacy. The task is to draw the attention of researchers, who previously were neglecting the problem of the loss of privacy, which is not only applicable to the virtual life, but also has a significant impact on the functioning offline. Two directions here are the most visible. Users, for the privilege, comfort, or just entertainment, share on the network more and more detailed information about themselves. At the same time the giants of the Internet, as well as governments, increase the scope of their surveillance, which may stand up to even the most aware and cautious person. Changes occur extremely quickly, and this is why publications a few years or even months ago rarely mentioned about problem, and then only briefly, which may be caused by insufficient awareness about its importance and its possible impact on developing societies. However, we cannot forget about increasing the awareness of modern societies, which results in the emergence of tools for privacy protection created by the users themselves.